Prenatal and progressive coenzyme Q10 administration to mitigate muscle dysfunction in mitochondrial disease - Juan Diego Hernández‐Camacho; Cristina Vicente‐García; Lorena Ardila‐García; Ana Padilla‐Campos; Guillermo López‐Lluch; Carlos Santos‐Ocaña; Peter S. Zammit; Jaime J. Carvajal; Plácido Navas; Daniel J.M. Fernández‐Ayala (Journal of Cachexia, Sarcopenia and Muscle)
Abstract Background ADCK genes encode aarF domain‐containing mitochondrial kinases involved in coenzyme Q (CoQ) biosynthesis and regulation. Haploinsufficiency of ADCK2 in humans leads to adult‐onset physical incapacity with reduced mitochondrial CoQ levels in skeletal muscle, resulting in mitochondrial myopathy and alterations in fatty acid β‐oxidation. The sole current treatment for CoQ deficiencies is oral administration of CoQ10, which causes only partial recovery with postnatal treatment, underscoring the importance of early diagnosis for successful intervention. Methods We used Adck2 heterozygous mice to examine the influence of this gene on muscle structure, function and regeneration throughout development, growth and ageing. This investigation involved techniques including immunohistochemistry, analysis of CoQ levels, mitochondrial respiratory content, muscle transcriptome analysis and functional tests. Results We demonstrated that Adck2 heterozygous mice exhibit defects from embryonic development, particularly in skeletal muscle (1102 genes deregulated). Adck2 heterozygous embryos were 7% smaller in size and displayed signs of delayed development. Prenatal administration of CoQ10 could mitigate these embryonic defects. Heterozygous Adck2 mice also showed a decrease in myogenic cell differentiation, with more severe consequences in ‘aged’ mice (41.63% smaller) (P < 0.01). Consequently, heterozygous Adck2 mice displayed accelerated muscle wasting associated with ageing in muscle structure (P < 0.05), muscle function (less grip strength capacity) (P < 0.001) and muscle mitochondrial respiration (P < 0.001). Furthermore, progressive CoQ10 administration conferred protective effects on mitochondrial function (P < 0.0001) and skeletal muscle (P < 0.05). Conclusions Our work uncovered novel aspects of CoQ deficiencies, revealing defects during embryonic development in mammals for the first time. Additionally, we identified the gradual establishment and progression of the deleterious Adck2 mouse phenotype. Importantly, CoQ10 supplementation demonstrated a protective effect when initiated during development.